Selection of a culture medium for the growth of Pichia guilliermondii LEVICA- 27 as activator additive of ruminal fermentation - González, Bexy; Sosa, Dailyn; Marrero, Yoandra; García, Yaneisy; Albelo, Nereyda (Cuban Journal of Agricultural Science, 2022)
In order to select a non-conventional culture medium for the growth of Pichia guilliermondii LEVICA-27 as an activator additive for ruminal fermentation, two trials were carried out in which YPG medium was used (yeast extract 10 g/L, peptone 10 g/L and glucose 20 g/L) as control medium. In the first, seven culture media were evaluated for yeast growth at 24 hours of fermentation. While in the second, growth kinetics was performed in the selected medium of the first test. In addition, in the latter, the maximum specific growth rate, the biomass doubling time, and the stoichiometric balance of the selected medium were determined. At 24 hours of fermentation, there were not differences between the media studied and the YPG medium (p=0.073). Therefore, the latter can be replaced without affecting the strain growth in 24 h. In the kinetic study, there was a higher microbial concentration at 12 h (P<0.0001) in the medium containing molasses and urea. The maximum specific growth rate was lower (P=0.0260) and the biomass doubling time was higher (P=0.0283) with respect to the control. The selected medium constitutes an adequate option for the production of LEVICA-27, since it allows obtaining good cell concentration, covering the nutritional requirements and includes fewer components in its preparation. This offers economic and operational advantages for obtaining the additive at production scales. Key words: molasses, yeast, fermentation, biomass.